Representasi Pengalaman Spasial di Media Sosial Instagram:: Kasus Koridor Belanja Tradisional Malioboro Yogyakarta - Rahadiyanti, Melania; Kusumowidagdo, Astrid (EMARA: Indonesian Journal of Architecture, 2022)
This research aimed to examine the representation of a sense of place for a traditional shopping place on social media, both in the form of visual and narrative media. The research object was the Malioboro shopping area as represented on social media posts. The theoretical contribution of this research is as a literature review on the representation of sense of place in the Malioboro shopping area, while the practical contribution of this research is as a reference for policymakers or the government in formulating the development policy of traditional shopping streets on social media. This research was qualitative in nature, with Instagram as the data source. All posts and videos with captions were analyzed to explore the Malioboro Corridor’s physical attributes, social activities, and shared meaning. In conclusion, the three dimensions of a sense of place regarding the local conditions were presented in Instagram content..